Analisis Corporate Social Responsibility Terhadap Green Technology Innovation Dengan Pengendalian Internal Sebagai Variabel Intervening - Putri Hardian, Qanita Marsha; Suryaningrum, Diah Hari (Universitas Gorontalo, 2024)
This research investigates the influence of Corporate Social Responsibility (CSR) on Green Technology Innovation, towards Internal Control as an intervening variable. This studies is quantitative and focuses on companies in the energy, industrial, materials, and infrastructure sectors on the Indonesia Stock Exchange from 2018 to 2022. This study using the statistic descriptive method. The research results show that CSR as an independent variable and Internal Control as an intervening variable influence Green Technology Innovation. This study suggests that companies, shareholders, and governments should consider environmental risks in their decision-making processes.